Nodular Cystic Basal Cell Carcinoma of the Trunk: a Diagnostic Dilemma in an Unsuspecting Youth - Ruchita Tyagi; Dilpreet Kaur; Gursheen Kaur; Bhavna Garg; Neena Sood; Sunil Gupta (Iranian Society of Pathology, 2017)
Basal cell carcinoma (BCC) commonly affects the elderly and is mostly confined to the head and neck region. Only 10% of all cases occur on the trunk. We presented a case of bullous lesion on the abdomen in a young male, initially diagnosed by clinicians as a vascular nevus. Histopathological examination and immunohistochemistry (IHC) revealed it to be Nodular cystic variant of BCC. This rare variant of BCC morphologically resembles benign skin adnexal tumor of Eccrine syringofibroadenoma. Ber Ep4 positivity on IHC established the correct diagnosis. This case highlights that nodular cystic variant of BCC can be a diagnostic dilemma for clinicians and pathologists.